?CHROMIUM IN SEDIMENT OF THE MOVING STREAM OF TANNERY WASTE- FROM SECTOR 7-A OF KORANGI INDUSTRIAL AREA TO ARABIAN SEA. - IQBAL, MUHAMMAD (Biological Sciences - PJSIR, 1995)
Chromecompoundsareincludedin thecategoryofheavymetalderivativesandthusarepartofagroupwhichmust be kept out of the environment.Tanneries, locatedin sector7-A of Korangi industrial area of Karachi, aredischarg- ing their eft1uentwithout anytreatment.This effluentcarrieschromium,used inthetanning process, towards the sea. Dueto mixingofdifferentstreamsoftannerywasteintothedrain,mostofthechrominumsettlesdownin sedimentand leavesvery littlechromium inliquid.Sampleswerecollectedtocheckchromiuminsedimentsin thestreamoftannery eft1uent,from thesourceofdischarge, sector 7-Atothesea.Ithas beenfoundthat after somedistancethe chromium in wastewater become undetectable which shows almost complete settling of chromium into the sediment. Results showed that even at 10Km awayfrom the source,considerable quantityof chromium was foundto be present in the sediment, which reveal that sludge formed during the mixing is travelling toward the sea and contaminating it with chromium.